SISTEM PAKAR PENDETEKSI KERUSAKAN MESIN PACKING OTOMATIS MODEL CP730B DENGAN METODE CASE BASED REASONING - Yoga Religia; Erni Ratnasari2 (Jurnal SIGMA, 2019)
In this study the problem was formulated about the proccess how to implement the Decision Support System using the Case Based Reasoning Method to detect damage to an automatic CP730B packing machine. While the purpose of this research is to design a system that can be used to detect damage to machines that often occur, find solutions to make it easier for technicians and production employees who use the CP730B model automatic packing machine to save time, effort and how to minimize the expense of maintenance costs. This system is made using PHP, for its Database using MySql Database and the method used in making this system is the Case Based Reasoning method. His system pupose provides knowledge of the symptoms of damage to the machine as well as solitions to how to deal with damage so as to reduce the maintenace cost budget by specialized technicians because almost all of the handling can be done alone using this system. The result of this system is to assist in the detection of breakages or problems that occur in an automatic packing machine. Keywords : Expert System, Case Base Reasoning, Php, Mysql Database.